PENGGUNAAN MEDIA AUDIO VISUAL DALAM PENGENALAN BACAAN DAN GERAKAN SHALAT DI RA SYIHABUDDIN LANDUNGSARI MALANG - Eka Rosadah; Anwar Sa’dullah; Eko Setiawan (Jurnal Dewantara, 2021)
This study amis to describe the use of audio-visual media in the introduction of reading and prayer movements of students of RA Syihabuddin Landungsari Malang. This study uses a descriptive qualitative approach. The research subjects were kindergarten A and B, homeroom teachers, curriculum teachers, and students guardians. The results of this study indicate that the ability to recognize reading and prayer movements that have been achieved by each student varies according to the age level of students. The results of the process of using videos in the introduction of reading and prayer movements are carried out through sending learning videos through the whatsapp group which are procedures for introducing reading and prayer movements demonstrated by educators. The results of the obstacles in the use of learning videos to introduce reading and prayer movements are (1) students are less focused in learning and are bored. (2) educators are less able to introduce perfect prayer movements. (3) lack of adequate mobile phones and cellular networks. (4) parents who have not been able to guide their children in doing school assignments. So it can be concluded that the use of learning videos to introduce reading and prayer movements has not been able to be understood by students.